Kinetic Analysis of the Effect of pH on Biogas Production from Cow Manure Waste through Anaerobic Processes - Priyatna, Aufa Irsyad; Firdaus, Alzena Nasywa; Sa'diyah, Siti Halimatu; Syaichurrozi, Iqbal (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2025)
Biogas is the decomposition of organic waste by bacteria through an anaerobic fermentation process that can be managed to produce biogas in the form of methane gas (CH4). This study aims to analyze the effect of pH variation on biogas production through anaerobic digestion using a kinetic modeling approach. Using secondary data from previous studies, three kinetic models Gompertz, First Order, and Logistic were applied to predict biogas volume at acidic pH 4.52, neutral (6.80), and alkaline (8.52). Alkaline pH (8.52) resulted in the highest biogas production at 2850 mL. At pH 8.52, Gompertz parameters such as production potential (4,231.24 mL), maximum rate (163.19 mL/day), and shortest lag phase (3.92 days) indicated the highest efficiency.